Cryptococcus neoformans Recovered From Olive Trees (Olea europaea) in Turkey Reveal Allopatry With African and South American Lineages - Ergin, Çağri; Şengül, Mustafa; Aksoy, Levent; Döğen, Aylin; Sun, Sheng; Averette, Anna F.; Cuomo, Christina A.; Seyedmousavi, Seyedmojtaba; Heitman, Joseph; Ilkit, Macit (Frontiers in Cellular and Infection Microbiology, 2019)
Cryptococcus species are life-threatening human fungal pathogens that cause cryptococcal meningoencephalitis in both immunocompromised and healthy hosts. The natural environmental niches of Cryptococcus include pigeon (Columba livia) guano, soil, and a variety of tree species such as Eucalyptus camaldulensis, Ceratonia siliqua, Platanus orientalis, and Pinus spp. Genetic and genomic studies of extensive sample collections have provided insights into the population distribution and composition of different Cryptococcus species in geographic regions around the world. However, few such studies examined Cryptococcus in Turkey. We sampled 388 Olea europaea (olive) and 132 E. camaldulensis trees from seven locations in coastal and inland areas of the Aegean region of Anatolian Turkey in September 2016 to investigate the distribution and genetic diversity present in the natural Cryptococcus population. We isolated 84 Cryptococcus neoformans strains (83 MATα and 1 MATa) and 3 Cryptococcus deneoformans strains (all MATα) from 87 (22.4% of surveyed) O. europaea trees; a total of 32 C. neoformans strains were isolated from 32 (24.2%) of the E. camaldulensis trees, all of which were MATα. A statistically significant difference was observed in the frequency of C. neoformans isolation between coastal and inland areas (P < 0.05). Interestingly, the MATaC. neoformans isolate was fertile in laboratory crosses with VNI and VNB MATα tester strains and produced robust hyphae, basidia, and basidiospores, thus suggesting potential sexual reproduction in the natural population. Sequencing analyses of the URA5 gene identified at least five different genotypes among the isolates. Population genetics and genomic analyses revealed that most of the isolates in Turkey belong to the VNBII lineage of C. neoformans, which is predominantly found in southern Africa; these isolates are part of a distinct minor clade within VNBII that includes several isolates from Zambia and Brazil. Our study provides insights into the geographic distribution of different C. neoformans lineages in the Mediterranean region and highlights the need for wider geographic sampling to gain a better understanding of the natural habitats, migration, epidemiology, and evolution of this important human fungal pathogen.